White Blood Cell Count and Major Adverse Cardiovascular Events After Percutaneous Coronary Intervention in the Contemporary Era: Insights From the PARIS Study (Patterns of Non-Adherence to Anti-Platelet Regimens in Stented Patients Registry). (September 2017) - Shah, Binita; Baber, Usman; Pocock, Stuart J.; Krucoff, Mitchell W.; Ariti, Cono; Gibson, C. Michael; Steg, Philippe Gabriel; Weisz, Giora; Witzenbichler, Bernhard; Henry, Timothy D.; Kini, Annapoorna S.; Stuckey, Thomas; et al.
Abstract : Background—: Elevated white blood cell (WBC) count is associated with increased major adverse cardiovascular events (MACE) in the setting of acute coronary syndrome. The aim of this study was to evaluate whether similar associations persist in an all-comers population of patients undergoing percutaneous coronary intervention in the contemporary era. Methods and Results—: In the multicenter, prospective, observational PARIS study (Patterns of Non-Adherence to Anti-Platelet Regimens in Stented Patients Registry), 4222 patients who underwent percutaneous coronary intervention in the United States and Europe between July 1, 2009, and December 2, 2010, were evaluated. The associations between baseline WBC and MACE (composite of cardiac death, stent thrombosis, spontaneous myocardial infarction, or target lesion revascularization) at 24-month follow-up were analyzed using multivariable Cox regression. Patients with higher WBC were more often younger, smokers, and with less comorbid risk factors compared with those with lower WBC. After adjustment for baseline and procedural characteristics, WBC remained independently associated with MACE (hazard ratio [HR] per 10 3 cells/μL increase, 1.05 [95% confidence intervals (CI), 1.02–1.09]; P =0.001), cardiac death (HR, 1.10 [95% CI, 1.05–1.17]; P <0.001), and clinically indicated target revascularization (HR, 1.04 [95% CI, 1.00–1.09]; P =0.03) but not stent thrombosis (HR, 1.07 [95% CI, 0.99–1.16]; P =0.10) or spontaneous myocardial infarction (HR, 1.03 [95% CI, 0.97–1.09]; P =0.29). The association between WBC and MACE was consistent in acute coronary syndrome and non–acute coronary syndrome presentations (interaction P =0.15). Conclusions—: Increased WBC is an independent predictor of MACE after percutaneous coronary intervention in a contemporary all-comers cohort. Further studies to delineate the underlying pathophysiologic role of elevated WBC across a spectrum of coronary artery disease presentations are warranted. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00998127. Abstract : Supplemental Digital Content is available in the text.